EFFECT OF ORGANIC AND INORGANIC FERTILIZERS OR THEIR COMBINATIONS ON YIELD AND QUALITY COMPONENTS OF OIL SEED SUNFLOWER IN A SEMI-ARID ENVIRONMENT - Öztürk, Erdoğan; Ozturk, Hatice; Polat, Taşkın; Sefaoglu, Firat; Toktay, Zehra; Sezek, Murat (Turkish Journal of Field Crops, 2021)
Producers in semi-arid and highland regions have difficulty in increasing diversity in crop rotations due to unfavorable conditions imposed by cool temperatures, inadequate rainfall, and shorter growing periods. In such conditions, some cultural practices that increase productivity such as fertilization appear as a promising alternative. Fertilization and the form of fertilizer have a substantial influence on sunflower (Helianthus annuus L.) seed yield and quality. The objective of this study was to determine the responses of the oilseed sunflower to organic (vermicompost and leonardite) and inorganic (nitrogen and phosphorus) fertilizers, or their combinations in a highland environment. To this end, the field research was carried out in 2017 and 2018 in Erzurum, Eastern Anatolia, Turkey. In this study, it was found that the organic and inorganic fertilizers alone and their combinations significantly affected all the plant parameters. The highest seed yield (4854 kg ha-1) and oil yield (2114 kg ha-1) were obtained from the combined use of nitrogen and vermicompost. Moreover, the use of vermicompost alone yielded the highest oil content (46.8%). According to the results of this study, combined applications of organic (vermicompost) and inorganic (nitrogen) fertilizers had the highest yield and agronomic characteristics in oilseed sunflower production; so, these applications can be recommended for the similar ecological conditions, that is, short growing season and high altitude.
Keywords: Helianthus annus L.; inorganik fertilizer; organiz fertilizer; sunflower; verimcompost; yield; yield components; 2. Zero hunger; 15. Life on land